Evaluation of Patient Reported Gastroesophageal Reflux Severity at Baseline and at 1-year After Bariatric Surgery. Issue 6 (17th June 2022) - Ehlers, Anne P.; Thumma, Jyothi R.; Finks, Jonathan F.; Carlin, Arthur M.; Ghaferi, Amir A.; Varban, Oliver A.
Abstract : Objective: To assess patient-reported gastroesophageal reflux disease (GERD) severity before and after SG and Roux-en-Y gastric bypass (RYGB). Summary of Background Data: Development of new-onset or worsening GERD symptoms after bariatric surgery varies by procedure, but there is a lack of patient-reported data to help guide decision-making. Methods: Retrospective cohort study of patients undergoing bariatric surgery in a statewide quality collaborative between 2013 and 2017. We used a validated GERD survey with symptom scores ranging from 0 (no symptoms) to 5 (severe daily symptoms) and included patients who completed surveys both at baseline and 1-year after surgery (n = 10, 451). We compared the rates of improved and worsened GERD symptoms after SG and RYGB. Results: Within our study cohort, 8680 (83%) underwent SG and 1771 (17%) underwent RYGB. Mean baseline score for all patients was 0.94. Patients undergoing SG experienced similar improvement in GERD symptoms when compared to RYGB (30.4% vs 30.8%, P = 0.7015). However, SG patients also reported higher rates of worsening symptoms (17.8% vs 7.5%, P < 0.0001) even though they were more likely to undergo concurrent hiatal hernia repair (35.1% vs 20.0%, P< 0.0001). More than half of patients (53.5%) did not report a change in their score. Conclusions: Although SG patients reported higher rates of worsening GERD symptoms when compared to RYGB, the majority of patients (>80%) in this study experienced improvement or no change in GERD regardless of procedure. Using clinically relevant patient-reported outcomes can help guide decisions about procedure choice in bariatric surgery for patients with GERD.